PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN BAGIAN PRODUKSI PT. PG RAJAWALI II UNIT PG JATITUJUH MAJALENGKA - Setyo Dwi Widyastuti; Muhamad Fauzi (JURNAL KESEHATAN INDRA HUSADA, 2017)
Occupational safety and occupational problems in Indonesia are still often ignored.This can be seen from the high rate of work accident. According to data from Jamsostek, the number of work accidents in 2012 as many as 9,056 cases of work accidents. Of these, 2,419 cases resulted in death. According Afdifar (2012), only 2.1% of the 15,000 large companies that implement K3 management system. While in small and medium enterprises, implementation of the implementation of K3 management system is also still far fromexpectations. Based on the measurement of the Employment Development Index (IPK), Indonesia in 2012, the indicator of Working Environment Condition only reached 3.71 (low) or decreased compared to 2011 which reached 5.02 index (medium-down) (Ilfani,2013). With the implementation of health and safety programs in the company is expected to improve the quality of employee performance and able to support the achievement of corporate objectives optimally.The purpose of this study was to determine the effect of occupational health and safety on the performance of employees of the production of PT. PG Rajawali II Unit PG Jatitujuh Majalengka. The research type is survey method with cross sectional approach. The population is all employees of production II PT. PT. PG Rajawali II Unit PG Jatitujuh Majalengka as many as 600 people. Sampling in this research is by quota accidental sampling technique, that is 87 people. The instrument used in this study is a questionnaire sheet and analyzed by using pearson correlation analysis technique.Based on the results of data analysis research, it can be seen that health and safety (K3) effect on employee Performance Part II PT. PG Rajawali II Unit PG Jatitujuh Regency Majalengka. This study only examines the effect of health and safety (K3) on employee performance, therefore it is expected the next researcher can deepen this research by adding other factors that may affect employee performance.